A Grammatical Analysis of Biseni Clause Structure - Worufah, Ebini-Ipiri Raphael; Ebitare Fabiawari Obikudo PHD (Periodica Journal, 2023)
This paper presents a grammatical description of the clause structure of Biseni; a dialect of Ijọ, spoken in Yenagoa Local Government Area of Bayelsa State. The paper establishes the typological classification of clauses and sentences based on syntactic properties and communicative functions, analyzes grammatical relationships that hold in intra-clausal strings and evaluate the peculiar movement operations attested in complex clause structures. Findings show a Subject-Object-Verb (SOV) word order for the basic clause structure, while attesting a Kẹ COMP that functions as a conjunct linking the embedded clause to the matrix and also as focus marker. A v-movement operation that is at variance with Ndimele (1994) and Koopman (1983) assertions on v-movement is revealed, as analyses show inter-clausal movement from v-position in SPEC-I' of the matrix clause to another v-position in SPEC-I' of the embedded clause in a rightward demotion operation. Focused elements are left in-situ, while topicalised constituents are moved from base generated position to pre-subject position through fronting. Question words in interrogative structures either remain in-situ in base generated nonsubject position or are moved rightward to a post-verbal position, devoid of AUX/Subject inversion or Do-insertion. Findings contribute to linguistic knowledge in the areas of theory, policy and pedagogy and are recommended to researchers interested in exploring the peculiarities of Biseni clause structure, as insights provided can serve useful educational purposes for national and multinational agencies interested in exploring the intricate idiosyncratic forms of Nigerian grammars and developing instructional materials for teaching and learning such grammars
Keywords: forms; materials; learning; idiosyncratic